(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
By the 1920s, the country’s life and the livelihood of the local population were in dire straits. The severe consequences of World War I, the brutal and brutal policies of the Bolshevik rulers against the local population during the establishment of the new Soviet system were evident at every step.